Pengaruh Limbah Keramik dan Abu Terbang Terhadap Kuat Tekan dan Daya Serap Air Bata Beton - Satya Adi Purnama; Tri Sudibyo (Departemen Teknik Sipil dan Lingkungan, IPB University, 2018)
The growth of development sector in Indonesia lead a high demand for cement and sand. The research was conducted from February to July 2018 with objectives of analyzing and knowing the influence of mixture of ceramic waste and fly ash on compressive strength and water absorption of paving block. The research was started from preparation of tools and materials, manufactured of specimens and also tested the compressive strength and absorption of paving block. Quality standardwere based on SNI 03-0691-1996. Based on the analysis result, the highest compressive strength of 26.56 Mpa was obtained from paving block with 9% fly ash and 6% ceramic waste and was classified as class B. The highest water absorption of 18.29% was paving block with 15% mixtured of ceramic wastes and the lowest water absorption of 9.65% was normal paving block. Brick concrete with 6% mixture of ceramic waste and 9% fly ash had several advantages, i.e. cheaper cost, had a higher compressive strength and higher water absorption compared to normal paving block, more environmental friendly, had lighter weight and ease of installation. Key words: ceramic wastes, compressive strength, fly ash, paving block, water absorption